1979
DOI: 10.1287/mnsc.25.10.990
|View full text |Cite
|
Sign up to set email alerts
|

An Indirect Method for the Generalized k-Median Problem Applied to Lock-Box Location

Abstract: The problem of locating lock-boxes (post office boxes operated by banks for corporations) has been formulated as an uncapacitated plant location problem, for which there exist many efficient methods. However, corporations are often reluctant to establish as many lock-boxes as indicated by the optimal solution to this formulation. Hence, it is advisable to find the sequence of solutions containing 1, …, m lock-boxes, where m denotes the optimal number for the uncapacitated problem. This can be done by imposing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1983
1983
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The technique of determining a solution with a prespecified number of established facilities (i. e. solving a "/?-median" problem) by varying the fixed costs of UFLPs has been proposed several times in literature [3,6,11,15,17]. To obtain a certain p value, two papers [11,17] independently suggested a scheme for updating y.…”
Section: Solution Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique of determining a solution with a prespecified number of established facilities (i. e. solving a "/?-median" problem) by varying the fixed costs of UFLPs has been proposed several times in literature [3,6,11,15,17]. To obtain a certain p value, two papers [11,17] independently suggested a scheme for updating y.…”
Section: Solution Approachmentioning
confidence: 99%
“…For this problem, severâl branch-and-bound algorithms have been proposed in literature: [9] is explicitly addressed to a fixed cost /j-median problem, while the solution methods [1,6,8,11] have to be modified slightly by introducing the facility costs f t . However, the reported expérience [11, 15,17] shows that the non-convex case occurs rather seldom when practical data is processed. So we can expect that, in the most situations, NFCLP will already be solved during phase (b).…”
Section: Basic Solution Proceduresmentioning
confidence: 99%
“…The papers by Kramer [15], Stancill [27], McAdams [19], Kraus, Jansen and McAdams [17], Shanker and Zoltners [26] and Maier and Vander Weide [20] fall in the first category. The papers by Baker, Maier and Vander Weide [1], Bulfin and Unger [3], Ciochetto, Swanson, Lee and Woolsey [5], Corneujols, Fisher and Nemhauser [7], Fielitz and White [11], Levy [18], Mavrides [22], Nauss and Markland [23] and Stone [31] fall in the second.…”
Section: The Lockbox Location Problemmentioning
confidence: 99%
“…We have generally recommended the use of the 1‐for‐1 and 2‐for‐2 interchange heuristics because they provide valuable information on both optimal and close‐to‐optimal solutions. However, we have also employed a Lagrangian Relaxation/Branch‐and‐Bound [22] procedure as a check on the heuristics. In the hundreds of studies we have done over the last seven years, we have never found a single instance in which the more elaborate optimization techniques found a superior solution to the heuristics.…”
Section: Optimization and Heuristic Algorithmsmentioning
confidence: 99%
“…The problem is formally defined as an integer programming problem with the aim to minimize the generated traffic. These kinds of problems have been shown to be NP-complete [4], [5]. It is a complex combinatorial problem involving selecting appropriate locations of the edge servers and then allocating the offloading jobs to these edge servers in a proper manner.…”
Section: Introductionmentioning
confidence: 99%